FAM210A is essential for cold-induced mitochondrial remodeling in brown adipocytes - Jiamin Qiu; Feng Yue; Peipei Zhu; Jingjuan Chen; Fan Xu; Lijia Zhang; Kun Ho Kim; Madigan M. Snyder; Nanjian Luo; Hao-wei Xu; Fang Huang; W. Andy Tao; et al. (Nature Communications, 2023)
Abstract Cold stimulation dynamically remodels mitochondria in brown adipose tissue (BAT) to facilitate non-shivering thermogenesis in mammals, but what regulates mitochondrial plasticity is poorly understood. Comparing mitochondrial proteomes in response to cold revealed FAM210A as a cold-inducible mitochondrial inner membrane protein. An adipocyte-specific constitutive knockout of Fam210a (Fam210a AKO ) disrupts mitochondrial cristae structure and diminishes the thermogenic activity of BAT, rendering the Fam210a AKO mice vulnerable to lethal hypothermia under acute cold exposure. Induced knockout of Fam210a in adult adipocytes (Fam210a iAKO ) does not affect steady-state mitochondrial structure under thermoneutrality, but impairs cold-induced mitochondrial remodeling, leading to progressive loss of cristae and reduction of mitochondrial density. Proteomics reveals an association between FAM210A and OPA1, whose cleavage governs cristae dynamics and mitochondrial remodeling. Mechanistically, FAM210A interacts with mitochondrial protease YME1L and modulates its activity toward OMA1 and OPA1 cleavage. These data establish FAM210A as a key regulator of mitochondrial cristae remodeling in BAT and shed light on the mechanism underlying mitochondrial plasticity in response to cold.